The more the merrier: SRG/eROSITA discovers two further galaxies showing X-ray quasi-periodic eruptions - Arcodia, R.; Liu, Z.; Merloni, A.; Malyali, A.; Rau, A.; Chakraborty, J.; Goodwin, A.; Buckley, D.; Brink, J.; Gromadzki, M.; Arzoumanian, Z.; Buchner, J.; et al. (2024)
X-ray quasi-periodic eruptions (QPEs) are a novel addition to the group of extragalactic transients. With only a select number of known sources, and many more models published trying to explain them, we are so far limited in our understanding by small number statistics. In this work, we report the discovery of two further galaxies showing QPEs, hereafter named eRO-QPE3 and eRO-QPE4, with the eROSITA X-ray telescope on board the Spectrum Roentgen Gamma observatory, followed by XMM-Newton, NICER, Swift-XRT, SALT (z., =., 0.024 and z., =., 0.044, respectively), and ATCA observations. Among the properties in common with those of known QPEs are: the thermal-like spectral shape in eruption (up to kT., ., 110 120 eV) and quiescence (kT., ., 50 90 eV) and its evolution during the eruptions (with a harder rise than decay); the lack of strong canonical signatures of active nuclei (from current optical, UV, infrared and radio data); and the low-mass nature of the host galaxies (logM∗., ., 9 10) and their massive central black holes (logMBH., ., 5 7). These discoveries also bring several new insights into the QPE population: (i) eRO-QPE3 shows eruptions on top of a decaying quiescence flux, providing further evidence for a connection between QPEs and a preceding tidal disruption event; (ii) eRO-QPE3 exhibits the longest recurrence times and faintest peak luminosity of QPEs, compared to the known QPE population, excluding a correlation between the two; (iii) we find evidence, for the first time, of a transient component that is harder, albeit much fainter, than the thermal QPE spectrum in eRO-QPE4; and (iv) eRO-QPE4 displays the appearance (or significant brightening) of the quiescence disk component after the detection of QPEs, supporting its short-lived nature against a preexisting active galactic nucleus. These new properties further highlight the need to find additional QPE sources to increase the sample size and draw meaningful conclusions about the intrinsic population. Overall, the newly discovered properties (e.g., recent origin and/or transient nature of the quiescent accretion disk; lack of correlation between eruption recurrence timescales and luminosity) are qualitatively consistent with recent models that identify QPEs as extreme mass-ratio inspirals.